Comprehensive review of adverse reactions and toxicology in ASO-based therapies for Duchenne Muscular Dystrophy: From FDA-approved drugs to peptide-conjugated ASO - Umme Sabrina Haque; Melissa Kohut; Toshifumi Yokota (Current Research in Toxicology)
Duchenne Muscular Dystrophy (DMD) is a devastating X-linked genetic disorder characterized by progressive muscle degeneration due to mutations in the dystrophin gene. This results in the absence or dysfunction of the dystrophin protein, leading to muscle weakness, loss of ambulation, respiratory issues, and cardiac complications, often leading to premature death. Recently, antisense oligonucleotide (ASO)-mediated exon skipping has emerged as a promising therapeutic strategy for DMD. Notably, the FDA has conditionally approved four ASO therapies for DMD, with numerous others in various stages of clinical development, indicating the growing interest and potential in this field. To enhance ASO-based therapies, researchers have explored the novel concept of conjugating peptides to the phosphorodiamidate morpholino backbone (PMO) of ASOs, leading to the development of peptide-conjugated PMOs (PPMOs). These PPMOs have demonstrated significantly improved pharmacokinetic profiles, potentially augmenting their therapeutic effectiveness. Despite the optimism surrounding ASOs and PPMOs, concerns persist regarding their efficacy and safety. To comprehensively evaluate these therapies, it is imperative to expand patient populations in clinical trials and conduct thorough investigations into the associated risks. This article provides a comprehensive review and discussion of the available data pertaining to adverse reactions and toxicology associated with FDA-approved ASO drugs for DMD. Furthermore, it offers insights into the emerging category of peptide-conjugated ASO drugs those are clinical and preclinical trials, shedding light on their potential benefits and challenges.